2021
DOI: 10.12944/cwe.16.2.11
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Socio-Economic Impact of Soft Approaches of Climate Adaptation using Changing Fuel Practice in Indoor Air at Rural Sites in India

Abstract: Majority of India’s rural population depends on biomass burning for cooking and heating purposes on traditional cook stoves called Chullah which results into indoor air pollution. The sampling for this study was carried out in two villages of India viz. Budhwada, Madhya Pradesh (M.P.) and Baggi, Himachal Pradesh (H.P.). Both the regions are significantly different in terms of culture, traditions, topography and daily practices and hence this study helped in understanding the contrast between these regions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
0
0
Order By: Relevance
“…A study by Singh et al (2014) has also shown significant reductions in aerosols and gaseous pollutant when an improved cookstove was used in place of the traditional one. Despite having the option to use cleaner fuel for cooking, like LPG in this case, people in rural areas still prefer food cooked on chullah due to their deep-rooted familiarity with its taste, thus showing reluctance to change their practices (Verma and Kulshrestha, 2021).…”
Section: Tf and Lp Approaches At Budhwadamentioning
confidence: 99%
“…A study by Singh et al (2014) has also shown significant reductions in aerosols and gaseous pollutant when an improved cookstove was used in place of the traditional one. Despite having the option to use cleaner fuel for cooking, like LPG in this case, people in rural areas still prefer food cooked on chullah due to their deep-rooted familiarity with its taste, thus showing reluctance to change their practices (Verma and Kulshrestha, 2021).…”
Section: Tf and Lp Approaches At Budhwadamentioning
confidence: 99%